Central nervous system-related safety and tolerability of add-on ketamine to antidepressant medication in treatment-resistant depression: focus on the unique safety profile of bipolar depression - Adam Włodarczyk; Wiesław J. Cubała; Maria Gałuszko-Węgielnik; Joanna Szarmach (SAGE Publishing, 2021)
Background: There is evidence supporting the use of ketamine in treatment-resistant depression (TRD). However, there are some safety and tolerability concerns associated with ketamine. This study aimed to investigate ketamine's safety and tolerability to the central nervous system and to assess the relationship between dissociative symptomology and psychometric outcomes during and after intravenous ketamine treatment concurrent with treatment by varying psychotropic medications in treatment-refractory inpatients with major depressive disorder (MDD) and bipolar disorder (BP). Methods: A total of 49 patients with MDD and BP were included in this study. The subjects were administered ketamine and were assessed for changes using an observational protocol. Results: No antidepressants were associated with psychomimetic symptomatology except for citalopram ( p  = 0.019). Patients treated with citalopram showed a higher intensity of psychomimetic symptomatology. The use of classic mood-stabilizers was significantly associated with an increase in psychomimetic symptomatology according to the Brief Psychiatric Rating Scale (BPRS; lamotrigine p  = 0.009, valproate p  = 0.048, lithium p  = 0.012). No sequelae were observed. Conclusions: Despite the limitations that this study may be underpowered due to the small sample size, the sample consisted of a heterogeneous TRD population in a single site, and there no blinding of who underwent only acute ketamine administration, our observations indicate ketamine use requires close safety and tolerability monitoring with regards to psychomimetic and dissociative symptoms in TRD-BP and careful management for MDD patients. ClinicalTrials.gov identifier: NCT04226963